Students’ Writing Competence of the Fourth Semester Students of English Department of Tidar University in Academic Year 2014/2015 - Bondan Eri Christianto; Yuyun Yulia (Universitas Sarjanawiyata Tamansiswa, 2018)
Meaning plays an important role for communication. This research is aimed at describing interpersonal, ideational and textual meanings found in the students’ hortatory exposition texts. The method of this research is a discourse analysis which analyzed meanings. The interpersonal meaning is to analyze the Mood and Modality; the ideational meaning is Transitivity; and the Textual meaning is Thematic Structure. The result of the research showed three points of conclusion. First, in terms of interpersonal meaning, it shows that the students used Declarative Mood types in their texts to give information. Most of the students used simple present tense to give related information based on the topic. Most of the students used high nominalization as the subjects of their clauses. This implies that the texts are in the form of written texts. Second, transitivity system is about people activities in particular place and time. It can be seen from the occurrence of the dominant use of of material process, relational process, and circumstance of location. Third, thematic structure showed that the clauses mostly used ideational theme. The reseacher found that the most dominant theme was the unmarked theme. It implies that the students used high nominalization because they frequently used subjects and circumstances as the nominalization in the beginning of the clauses. Thus, it is expected that metafunctions can improve students’ writing competence in the form of meaningful texts.